2014
DOI: 10.15252/embj.201386433
|View full text |Cite
|
Sign up to set email alerts
|

Eaf5/7/3 form a functionally independent NuA4 submodule linked to RNA polymerase II ‐coupled nucleosome recycling

Abstract: The NuA4 histone acetyltransferase complex is required for gene regulation, cell cycle progression, and DNA repair. Dissection of the 13-subunit complex reveals that the Eaf7 subunit bridges Eaf5 with Eaf3, a H3K36me3-binding chromodomain protein, and this Eaf5/7/3 trimer is anchored to NuA4 through Eaf5. This trimeric subcomplex represents a functional module, and a large portion exists in a native form outside the NuA4 complex. Gene-specific and genome-wide location analyses indicate that Eaf5/7/3 correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
100
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(121 citation statements)
references
References 101 publications
(196 reference statements)
14
100
1
2
Order By: Relevance
“…This is unsurprising, however, as other studies have shown that HAT occupancy is a poor predictor of histone acetylation (Xue-Franzén et al 2010;Rossetto et al 2014). Instead, these results suggest that there is a level of regulation of histone acetylation that is independent of HAT recruitment.…”
Section: Discussionmentioning
confidence: 85%
“…This is unsurprising, however, as other studies have shown that HAT occupancy is a poor predictor of histone acetylation (Xue-Franzén et al 2010;Rossetto et al 2014). Instead, these results suggest that there is a level of regulation of histone acetylation that is independent of HAT recruitment.…”
Section: Discussionmentioning
confidence: 85%
“…Tandem affinity purification of complexes was performed as described previously (39) with a few modifications reported elsewhere (12,20). Cultures of 250 ml of exponentially growing cells were harvested at an OD 600 of 1 to 2 and washed in 10 mM Tris, pH 8, 350 mM NaCl, and cell lysis was achieved with glass beads at 4°C in lysis buffer (10 mM Tris-HCl, pH 8, 350 mM NaCl, 10% glycerol, 0.1% NP-40, 1 mM PMSF, 0.5 mM dithiothreitol [DTT], 2 g/ml pepstatin, 2 g/ml leupeptin, 5 g/ml aprotinin, 5 mM ␤-glycerophosphate, 5 mM Na butyrate).…”
Section: Figmentioning
confidence: 99%
“…Chromatin immunoprecipitations were performed essentially as previously described (20). Chromatin samples were prepared from 200 ml of exponentially growing cells using the standard protocol.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations